'Painting within itself': The 'John Moores Liverpool Exhibition'. (1st October 2018) - Gee, Gabriel N.
This article takes at its cue the 1969 decision of the John Moores Liverpool Painting Prize and exhibition to exclude works projecting more than six inches out of the wall. The refusal to include British contemporary pictorial explorations that expanded beyond the frame of the canvas at the time can be seen as a conservative stance. However, it also paved the way for the exhibition's subsequent showcasing of the specific problems located within the internal space and constraints of the canvas, in an epoch that heralded the medium's obsolescence. First, we look at the relation between painting and sculpture in the first years of the biannual prize, when an independent sculpture section attested to latent concerns about the international standing of British arts. We then focus on the 1969 John Moores' exhibition that provides a unique perspective into the radical changes occurring in art practices in Britain at the time. Finally, we evoke a range of pictorial practices displayed at the John Moores in the 1970s, which are described as articulating a turn 'within itself', furthering an investigation into a range of specific aesthetic problems posed by the format of the canvas at the time.